Application of wMelPop Wolbachia Strain to Crash Local Populations of Aedes aegypti. - Scott A Ritchie; Michael Townsend; Chris J Paton; Ashley G Callahan; Ary A Hoffmann (Public Library of Science (PLoS), 2015)
The endosymbiotic bacteria Wolbachia pipientis (wMel strain) has been successfully established in several populations of Aedes aegypti, the primary dengue vector. The virulent Wolbachia strain wMelPop is known to cause several pathological impacts (increased egg mortality, life shortening, etc.) reducing overall fitness in the mosquito Ae. aegypti. Increased egg mortality could substantially reduce egg banks in areas with a lengthy monsoonal dry season, and be employed to eliminate local populations. We tested this application under semi-field cage conditions. First, we determined that wMelPop infection significantly reduced the survival of desiccation-resistant eggs of the dengue vector Ae. aegypti, with shade and temperature having a significant impact; nearly all wMelPop-infected eggs failed to hatch after 6 and 10 weeks in summer and winter conditions, respectively. In laboratory selection experiments we found that egg desiccation resistance can be increased by selection, and that this effect of wMelPop infection is due to the nuclear background of the host rather than Wolbachia. We then conducted an invasion of wMelPop within a semi-field cage using sustained weekly releases of wMelPop infected mosquitoes, with fixation achieved after 9 weeks. The egg populations wMelPop infected and an uninfected control were then subjected to a simulated prolonged monsoonal dry season (2.5 months) before flooding to induce hatching. The wMelPop infected eggs suffered significantly greater mortality than the controls, with only 0.67% and 4.35% of respective infected and uninfected eggs held in 99% shade hatching after 80 days. These studies suggest that wMelPop could be used to locally eliminate populations of Ae. aegypti that are exposed to prolonged dry conditions, particularly if combined with vector control.